Leadershıp in the Context of Socıal Capıtal in Educatıon - CÖMERT, Melike; YILDIZ, Emrah (Journal of Posthumanism, 2025)
In this study, the concept of social capital is defined, the importance of social capital in education and how to develop social capital in the context of leadership are discussed. In order to develop social capital, it is necessary to create an environment of trust in the school, to develop and encourage communication among the members of the organization, to prepare social environments where members can come together, to disseminate organizational stories that are an element of the organizational culture and to encourage cooperation. The development of social capital has a priority place among the leadership roles of school administrators. This study explores the impact of school principals' favoritism on teachers' organizational commitment, focusing on how favoritism influences teachers' emotional and professional attachment to their schools. Favoritism, in the context of educational leadership, can take many forms, such as giving preferential treatment to certain teachers in terms of promotions, assignments, or recognition, and it has been shown to create various challenges within the school environment. The research aims to understand how favoritism, whether perceived or real, affects teachers' sense of responsibility, job satisfaction, and their willingness to remain dedicated to their school organizations. Additionally, the study found that favoritism fosters an atmosphere of division among staff members. Teachers who are not the recipients of favoritism often feel alienated, undervalued, or resentful, which can lead to an erosion of teamwork and collaboration within the school. In some extreme cases, the erosion of trust can lead to high turnover rates and the loss of experienced, dedicated educators.